2003
DOI: 10.1126/science.1080216
|View full text |Cite
|
Sign up to set email alerts
|

Nitriding Iron at Lower Temperatures

Abstract: The microstructure in the surface layer of a pure iron plate was refined at the nanometer scale by means of a surface mechanical attrition treatment that generates repetitive severe plastic deformation of the surface layer. The subsequent nitriding kinetics of the treated iron with the nanostructured surface layer were greatly enhanced, so that the nitriding temperature could be as low as 300 degrees C, which is much lower than conventional nitriding temperatures (above 500 degrees C). This enhanced processing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
308
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 597 publications
(319 citation statements)
references
References 13 publications
10
308
0
1
Order By: Relevance
“…9,10 Therefore, understanding the underlying mechanisms of grain refinement induced by plastic straining is crucial, especially at the nanometer scale. On one hand, understanding the mechanism of strain-induced grain refinement is crucial for development of synthesis techniques that are oriented toward practical applications for engineering materials.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Therefore, understanding the underlying mechanisms of grain refinement induced by plastic straining is crucial, especially at the nanometer scale. On one hand, understanding the mechanism of strain-induced grain refinement is crucial for development of synthesis techniques that are oriented toward practical applications for engineering materials.…”
Section: Introductionmentioning
confidence: 99%
“…[30] Several studies have reported that surface mechanical attrition treatment (SMAT) produces a nanocrystalline layer on various surfaces by using balls (4-10 mm in diameter) to repeatedly and multi-directionally impact a work piece. [14,23] Although the grain refinement mechanism of the MSB technique is similar to that of SMAT, the energy of the shot particles ejected by MSB is far lower due to the smaller shot sizes (1.6 mm in diameter), and the shot impacts the workpiece multidirectionally during SMAT rather than unidirectionally during MSB. Therefore, it is more difficult to achieve surface nanocrystallization on a titanium plate using MSB than SMAT, but it is easier to achieve surface grain refinement.…”
Section: Resultsmentioning
confidence: 99%
“…[14,15] Currently, there are many severe plastic deformation (SPD) techniques for achieving surface nanocrystallization (SNC) on various materials, such as surface mechanical attrition treatment (SMAT), [16,17] surface mechanical grinding treatments (SMGT), [18] ultrasonic shot peening (USSP), [19,20] laser shock processing (LSP), [21] and high pressure torsion (HPT). [22] However, neither SNC nor enhanced kinetics have been studied on the surface of a large-sized titanium plate.…”
Section: Introductionmentioning
confidence: 99%
“…This technique is of great industrial interest as it forms a unique composite structure with a hard surface (nitride compounds layer) and tough interior so that the global mechanical performance and wear/corrosion resistance of alloys and steels could be greatly improved [1]. However, nitriding processes are performed at high temperatures (above 773 K) for a long duration (20 ∼ 80 h) and may induce serious deterioration of the substrate for many material families.…”
Section: Introductionmentioning
confidence: 99%